2019
DOI: 10.1002/1873-3468.13437
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus nonstructural protein 5 residue R681 is critical for dimer formation and enzymatic activity

Abstract: Zika virus (ZIKV) relies on its nonstructural protein 5 (NS5) for capping and synthesis of the viral RNA. Recent small‐angle X‐ray scattering (SAXS) data of recombinant ZIKV NS5 protein showed that it is dimeric in solution. Here, we present insights into the critical residues responsible for its dimer formation. SAXS studies of the engineered ZIKV NS5 mutants revealed that R681A mutation on NS5 (NS5R681A) disrupts the dimer formation and affects its RNA‐dependent RNA polymerase activity as well as the subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Although the NLS function can be disrupted without affecting viral RNA synthesis by mutation of residues required for importin binding, mutation of R888, a residue completely conserved in all flaviviruses leads to nonviable DENV2 ( Tay et al 2013 ). In addition, NS5 dimerization has been observed in proteins from both DENV and ZIKV and could be required for the formation of a cooperative complex of MTase and RdRp, enabling capping of newly synthesized RNA emerging from the RdRp in trans by the MTase domain from the other monomer ( Klema et al 2016 ; Saw et al 2019 ). The C ter 18 region is often not resolved in crystal structures of flaviviral NS5 ( Yap et al 2007 ; Zhao et al 2015a ), except in the case where NS5 dimers were observed and the C ter 18 region contained an α helix that protruded from the NS5 molecule into the MTase domain of the interacting NS5 partner ( Klema et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the NLS function can be disrupted without affecting viral RNA synthesis by mutation of residues required for importin binding, mutation of R888, a residue completely conserved in all flaviviruses leads to nonviable DENV2 ( Tay et al 2013 ). In addition, NS5 dimerization has been observed in proteins from both DENV and ZIKV and could be required for the formation of a cooperative complex of MTase and RdRp, enabling capping of newly synthesized RNA emerging from the RdRp in trans by the MTase domain from the other monomer ( Klema et al 2016 ; Saw et al 2019 ). The C ter 18 region is often not resolved in crystal structures of flaviviral NS5 ( Yap et al 2007 ; Zhao et al 2015a ), except in the case where NS5 dimers were observed and the C ter 18 region contained an α helix that protruded from the NS5 molecule into the MTase domain of the interacting NS5 partner ( Klema et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, female and male chico mutants succumbed to ZIKV infection at a much faster rate compared to their background controls, indicating an essential role for chico in host immunity against ZIKV ( Figures 5C, D ). We then estimated ZIKV copy numbers in the infected flies compared to PBS control-treated flies at 4 days post injection using primer sequences against NS5, the largest and most critical nonstructural protein in the ZIKV replication complex ( 38 40 ). In corroboration with the previous findings, we found strongly elevated levels of ZIKV copies in both female and male chico mutants compared to their respective controls ( Figures 6B, D ).…”
Section: Resultsmentioning
confidence: 99%
“…A virion lacking NS5 is required to determine NS5 function together with the chance that no other ZIKV protein or viral factor contributes to the observed effects. Due to the importance of the ZIKV NS5 protein for viral replication [66,[170][171][172], it would be difficult to produce and expand delta-NS5 virions, and deleterious mutations in NS5 could abrogate ZIKV replication [173][174][175] or enhance its toxicity (i.e., NS5 2634 and 3328 mutations) [176], as it is not easy to obtain viral progeny (i.e., this virus could be toxic to bacteria and packaging cells) [176]. It is possible to nullify the toxic effect of NS5 in the bacteria used for the development of the infectious cDNA clone of ZIKV by sequence modification (i.e., inserting a second copy of the intron sequence after nucleotide position 8882 in NS5) [177], but this procedure does not delete NS5 from virions.…”
Section: Discussionmentioning
confidence: 99%